2020
DOI: 10.1136/thoraxjnl-2020-214626
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lung cancer risk model (PLCOM2012 and LLPv2) performance in a community-based lung cancer screening programme

Abstract: IntroductionLow-dose CT (LDCT) screening of high-risk smokers reduces lung cancer (LC) specific mortality. Determining screening eligibility using individualised risk may improve screening effectiveness and reduce harm. Here, we compare the performance of two risk prediction models (PLCOM2012 and Liverpool Lung Project model (LLPv2)) and National Lung Screening Trial (NLST) eligibility criteria in a community-based screening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…52,54 Consequently, older individuals and those with greater smoking exposures are more likely to be identified as being at 54 Prospective studies and pilots which enrolled screenees based on risk-prediction models indeed showed that the mean age and presence of comorbidities increased in the higher risk-groups. 88,89 However, the average age in these studies and pilots was around 65, at which the life-expectancy is 18-22 years. 90 In these studies, self-selection and physician-selection may have aided in reducing the uptake of screening in individuals with low life-expectancies; but within large-scale programs, the uptake of screening in individuals with limited lifeexpectancies may still be considerable.…”
Section: Choosing the Risk-thresholdmentioning
confidence: 88%
See 2 more Smart Citations
“…52,54 Consequently, older individuals and those with greater smoking exposures are more likely to be identified as being at 54 Prospective studies and pilots which enrolled screenees based on risk-prediction models indeed showed that the mean age and presence of comorbidities increased in the higher risk-groups. 88,89 However, the average age in these studies and pilots was around 65, at which the life-expectancy is 18-22 years. 90 In these studies, self-selection and physician-selection may have aided in reducing the uptake of screening in individuals with low life-expectancies; but within large-scale programs, the uptake of screening in individuals with limited lifeexpectancies may still be considerable.…”
Section: Choosing the Risk-thresholdmentioning
confidence: 88%
“…But, if individuals with limited life‐expectancies (<5 years) are excluded from screening, overdiagnosis could be substantially reduced (by over 65%) while moderately reducing the number of screens required (10%‐13% fewer) and retaining the life‐years gained by risk‐based screening 54 . Prospective studies and pilots which enrolled screenees based on risk‐prediction models indeed showed that the mean age and presence of comorbidities increased in the higher risk‐groups 88,89 . However, the average age in these studies and pilots was around 65, at which the life‐expectancy is 18‐22 years 90 .…”
Section: Identification Of Individuals Eligible For Screening Throughmentioning
confidence: 92%
See 1 more Smart Citation
“…Risk-prediction models have since also been used to identify eligible individuals in various trials and implementation pilots. The UK Lung Screen (UKLS) trial or the NLST-criteria in ever smokers (aged 55-74) from deprived areas showed significant variation in selecting those eligible for lung cancer screening between these different methods (41). Furthermore, risks for developing lung cancer will vary per person over time, due to changes in risk factors as smoking history, but also age.…”
Section: Risk-based Eligibilitymentioning
confidence: 99%
“… 57 Retrospective analysis found that within the group of patients with cancer diagnosed, PLCO M2012 and LLP v2 at a ≥2.5% risk threshold would have outperformed NLST generalised eligibility criteria that would have missed 18% of cancers. 58 Based on the success of this pilot, NHS England have commissioned a further 10 screening pilots across the country. 59…”
Section: Use Of Risk Prediction Models To Select Screening Participanmentioning
confidence: 99%